2014
DOI: 10.1088/0960-1317/24/5/055021
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost filler-dissolved process for fabricating super-hydrophobic poly(dimethylsiloxane) surfaces with either lotus or petal effect

Abstract: A low-cost filler (salt) water-dissolved method is developed to produce large-area and flexible super-hydrophobic surfaces by using poly(dimethylsiloxane) (PDMS) material. Five levels of salt grain sizes are used to examine the filler size effect on fabricating the super-hydrophobic surfaces and on the hydrophobic mechanism involved. The results show that the surfaces fabricated using grain sizes of 53-74 and 74-104 μm exhibit the lotus effect (cell adhesion (CA) > 150 • and self-adhesion (SA) < 10 • ); wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Similarly, the effect of surface roughness is not straightforward, as becomes obvious when comparing the ‘petal effect’ ( Feng et al , 2008 ; Janairo et al , 2016 ) and the ‘lotus effect’ ( Barthlott and Neinhuis, 1997 ; Schulte et al , 2011 ). In both cases, hierarchical surface structures result in apparent contact angles >150°, but depending on the aspect ratio, namely the height-to-distance ratio of the asperities, drops either stick or bead off ( Bhushan and Jung, 2008 ; Lin and Chou, 2014 ; Gong et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effect of surface roughness is not straightforward, as becomes obvious when comparing the ‘petal effect’ ( Feng et al , 2008 ; Janairo et al , 2016 ) and the ‘lotus effect’ ( Barthlott and Neinhuis, 1997 ; Schulte et al , 2011 ). In both cases, hierarchical surface structures result in apparent contact angles >150°, but depending on the aspect ratio, namely the height-to-distance ratio of the asperities, drops either stick or bead off ( Bhushan and Jung, 2008 ; Lin and Chou, 2014 ; Gong et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces with very large contact angles can be created in a variety of manners, in many cases inspired by Nature itself . For example, one may create a rough surface by abrading fluorinated hydrophobic materials or use particulates to create rough surfaces in curable liquid polymers such as polydimethylsiloxane. In the current study, abrasion is chosen since it can be applied with very simple means to existing surfaces to get reasonably repeatable results when it comes to surface statistics and wetting. This further allowed a study of the triboelectric charge that formed when water droplets moved over the rough surface with different types of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 7(a)-(c) shows the AFM topographies of the BNNT-PDMS nanocomposites surfaces. Pure PDMS resin does not exhibit a petal effect and surface texturing is required to display the phenomenon [16,19]. Figure 7(a) depicts the 3D surface of the nanocomposite with 0.5 wt% BNNT.…”
Section: Investigation Of the Wetting Regimementioning
confidence: 99%
“…Previous literature on this phenomenon involved experimental investigations on naturally available rose petals [10][11][12]. Petal effect can be achieved by having a rough [13,14] or textured surface [15][16][17]. To fabricate such surfaces, researchers have employed several techniques such as using natural rose petals [10,11,18] and sandpaper [19] as molds, plasma spraying [20], laser etching [21], electrospinning [22], and recently Zhen Shi et al suggested the technique of hydrocarbon adsorption to create such biomimetic surfaces [23].…”
Section: Introductionmentioning
confidence: 99%